2019
DOI: 10.23887/mkfis.v18i1.22234
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Value Clarification Technique Berbasis Tri Kaya Parisudha Terhadap Sikap Sosial Siswa Pada Mata Pelajaran PKN Kelas V

Abstract: ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran value clarification technique berbasis tri kaya parisudha terhadap sikap sosial siswa pada mata pelajaran PKn siswa kelas V SD Gugus VI Kecamatan Tegalalang. Jenis penelitian ini adalah eksperimen semu dengan rancangan non-equivalent post test only group design. Populasi dari penelitian ini adalah seluruh siswa kelas V SD Gugus VI Kecamatan Tegalalang tahun pelajaran 2018/2019 yang berjumlah 111 siswa. Sampel penelitian ini yaitu Kela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…(Muliawan et al, 2016) also state that Audio-visual learning model assisted time tokens can improve language skills in group B4 children in PAUD Kusuma II, West Denpasar. A study conducted by (Dewi et al, 2019) also state that the group of students who are taught using the Tri Kaya Parisudha based VCT learning model is better than the group of students who applied conventional learning model. It can be concluded that there was a significant effect of Tri Kaya Parisudha based VCT learning model on social attitudes of Civics in the fifthgrade elementary school.…”
Section: Table 03 Conversion With Pap Scalementioning
confidence: 97%
“…(Muliawan et al, 2016) also state that Audio-visual learning model assisted time tokens can improve language skills in group B4 children in PAUD Kusuma II, West Denpasar. A study conducted by (Dewi et al, 2019) also state that the group of students who are taught using the Tri Kaya Parisudha based VCT learning model is better than the group of students who applied conventional learning model. It can be concluded that there was a significant effect of Tri Kaya Parisudha based VCT learning model on social attitudes of Civics in the fifthgrade elementary school.…”
Section: Table 03 Conversion With Pap Scalementioning
confidence: 97%